Methodische Grundlagen und Anwendungen der Generalisierbarkeitstheorie in der betriebswirtschaftlichen Forschung - Martin Eisend (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2007)
Generalizability theory provides an alternative and more flexible approach for construct measurement than classical measurement theory. The theory takes into account several sources of error. Generalizability studies lead to results that allow for designing measurements that optimize the generalizability of results. The paper gives a short introduction into generalizability theory and summarizes applications of generalizability theory in business research.
Keywords: 330; Statistischer Test; Betriebswirtschaftslehre; Theorie